PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, MOTIVASI DAN KOMPENSASI TERHADAP EFEKTIVITAS KERJA KARYAWAN PT. PANDAAN MIGAS DI PANDAAN - jurnalpps pps; Noviyanti Agustia Hasyim; C. Sri Hartati; Ruddy Winarko (Jurnal Manajerial Bisnis, 2019)
The purpose of this study is to find out, describe and analyze the relationship of democratic leadership style, motivation and compensation to the work effectiveness of employees of PT. Pandaan Migas, East Java. This research is an explanatory research research. This research uses a quantitative approach with a questionnaire method. The population in this study were all employees of PT. Oil and Gas Pandaan totaling 53 people were also used as research samples. The results showed that both partially and simultaneously the variables of democratic leadership style, motivation and compensation had a significant influence on the work effectiveness of the employees of PT. Pandaan Migas in Pandaan.